Rethinking online friction in the information society. (March 2023) - Tomalin, Marcus
A recurrent mantra of the technology industry is that all forms of 'friction' should be eliminated from online interactions (especially commercial transactions). In this context, 'friction' refers to any unnecessary retardation of a process or activity that delays the user accomplishing a desired action. This broad category can therefore include online adverts that link to the wrong webpages, pop-up windows that block access to content or delays in the physical delivery of an ordered item. Although visions of a frictionless future have been common since at least 1995 (the year Bill Gates popularised the phrase 'friction-free capitalism'), the basic notion has remained unhelpfully vague. Accordingly, this article focuses specifically on the phenomenon of online friction (i.e. 'e-friction') and elaborates a typology of the main subtypes. An analytical framework of this kind makes it much easier to compare and contrast distinct kinds of e-friction, recognising that important differences distinguish those that are 'elective', 'non-elective', 'impeding', 'distracting' and so on. Having sketched a preliminary typology, the article reflects upon the ethical implications of the distinct varieties, and concludes by suggesting that there are several reasons why an entirely (e-)frictionless future is a profoundly disturbing one.